Understanding sleep quality among postoperative patients in Intensive Care Unit: A conceptual analysis approach - Nunung Nurhayati; Agung Waluyo; I Made Kariasa; Sali Rahadi Asih; Hening Pujasari; Bahrul Hayat (Jurnal Keperawatan Padjadjaran, 2025)
Background: Sleep quality is an important yet understudied element influencing postoperative recovery in intensive care units. Considering that there is a lack of consistent knowledge of the quality of sleep, it is difficult to establish appropriate tests and therapies. Objective: To do a conceptual analysis of sleep quality in postoperative intensive care units patients utilizing the Walker and Avant framework, delineating its qualities, antecedents, consequences, and empirical referents. Methods: This study used the Walker and Avant eight-step process for idea analysis, which included a systematic literature evaluation of papers published between 2020 and 2024 in databases such as PubMed, Scopus, ScienceDirect, and ProQuest. Data was evaluated to determine important defining qualities, causes, outcomes, and measurable indicators of sleep quality. Results: The analysis identified four defining attributes of sleep quality: sleep architecture, sleep disturbances, subjective experience, and physiological indicators. Antecedents included environmental noise, lighting, pain, anxiety, and frequent medical interventions. Poor sleep quality was associated with adverse outcomes such as increased delirium risk, delayed wound healing, and prolonged intensive care units      stays. Empirical referents included patient-reported tools like the Pittsburgh Sleep Quality Index, polysomnography, and actigraphy. Conclusion: Sleep quality is a multidimensional concept central to postoperative care in intensive care unit. Addressing environmental and psychological factors through targeted interventions can improve sleep quality and enhance recovery outcomes.